2017
DOI: 10.3892/mmr.2017.6952
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126 inhibits endothelial permeability and apoptosis in apolipoprotein E-knockout mice fed a high-fat diet

Abstract: Endothelial dysfunction and apoptosis have key roles in the initiation and progression of atherosclerosis (AS). AS has been demonstrated to be associated with a high-fat diet, which may increase endothelial permeability and apoptosis; however, the exact mechanisms underlying the development of AS remain poorly understood. MicroRNAs (miRNAs) are vital for the regulation of cardiovascular disease, and dysregulated miRNAs have been implicated in AS. The present study investigated whether miRNA (miR)-126 regulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…However, we need further studies since no significant changes were observed in the expression level of miR-126 after exposure to CS. Consistent with the present study, previous studies have shown that the miR-126 level was decreased in the aortas of ApoE KO mice fed a high-fat diet [ 45 ]. Conversely, other previous studies have shown that the miR-126 level was increased in the aortas of ApoE KO mice with superimposed chronic kidney disease [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, we need further studies since no significant changes were observed in the expression level of miR-126 after exposure to CS. Consistent with the present study, previous studies have shown that the miR-126 level was decreased in the aortas of ApoE KO mice fed a high-fat diet [ 45 ]. Conversely, other previous studies have shown that the miR-126 level was increased in the aortas of ApoE KO mice with superimposed chronic kidney disease [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, endothelial dysfunction is considered an early marker of atherosclerosis development (14). Different miRNAs, such as miR-21 (21), miR-126 (22)(23)(24), miR-146a (25) and miR-221 (26), regulate endothelial cell senescence, proliferation, and migration and influence inflammatory pathways initiated in endothelial cells. Members of the miR-181 family have been shown to suppress the inflammatory response of endothelial cells by targeting mediators of NF-kB pathways (27)(28)(29).…”
Section: The Role Of Mirnas In the Regulation Of Atherosclerosismentioning
confidence: 99%
“…There is growing evidence that miRNAs control these pathologic processes including endothelial dysfunction (miR let-7g, mir-17-3p, miR-31, miR-146a, miR-155, miR-181 family, miR-221/-222,) [170][171][172][173][174][175], oxidative stress (miR-let-7a/b, miR-19b, miR-20a, miR-98, miR-126, miR-142-3p, miR-199a-3p and -5p, miR-200c, miR-221, miR-222, miR-328) [176][177][178][179][180][181][182][183][184][185][186][187][188][189], monocyte recruitment, differentiation and activation (miR-21, miR-23a-5p, miR-27a/b, miR-33, miR-34, miR-146a, miR-155, miR-212, miR-451, miR-590, miR-758-5p, [190][191][192][193][194][195][196][197][198][199][200][201] and inflammation/secretion of inflammatory cytokines (miR let-7g, miR-17-3p, miR-31, miR-146a, miR-155, miR-181a-3p/-5p, miR-181b, miR-221 and miR-222) [171,202,203]. Interestingly, a number of them are simultaneously involved in all those processes, suggesting common and/or cooperative activities, and underlying their relevance in the physiopathology of CVD.…”
Section: Cellular Micrornas As Biomarkers Of Cardiovascular Disease Imentioning
confidence: 99%